2008
DOI: 10.1099/vir.0.2008/001404-0
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-6-phosphate dehydrogenase deficiency enhances enterovirus 71 infection

Abstract: Variations in the cellular microenvironment affect the host's susceptibility to pathogens. Using glucose-6-phosphate dehydrogenase (G6PD)-deficient fibroblasts as a model, this study demonstrated that the cellular redox status affects infectivity as well as the outcome of enterovirus 71 (EV71) infection. Compared with their normal counterparts, G6PD-deficient cells supported EV71 replication more efficiently and showed greater cytopathic effect and loss of viability. Mechanistically, viral infection led to inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
84
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(88 citation statements)
references
References 50 publications
(44 reference statements)
2
84
1
1
Order By: Relevance
“…This haplotype has very low frequency in Caucasian populations but 17-35% frequency in Asian populations [7]. In addition, in vitro ana lysis suggests that glucose-6-phophate dehydrogenase deficiency enhances HEV71 infection [8]. A Taiwanese group demonstrated that children with severe forms of HEV71 encephalitis were significantly more likely to possess a specific cytotoxic T lymphocyte antigen haplotype (CTLA-4) than children who developed mild HEV71 infections [9].…”
Section: Epidemiologymentioning
confidence: 99%
“…This haplotype has very low frequency in Caucasian populations but 17-35% frequency in Asian populations [7]. In addition, in vitro ana lysis suggests that glucose-6-phophate dehydrogenase deficiency enhances HEV71 infection [8]. A Taiwanese group demonstrated that children with severe forms of HEV71 encephalitis were significantly more likely to possess a specific cytotoxic T lymphocyte antigen haplotype (CTLA-4) than children who developed mild HEV71 infections [9].…”
Section: Epidemiologymentioning
confidence: 99%
“…5, 6, 7, 8, 9 However, during the past decade, accumulating evidence has demonstrated that G6PD deficiency also affects nucleated cells 10, 11, 12, 13, 14 and cellular pathophysiological events, including dysregulated cell proliferation, accelerated cellular senescence, enhanced susceptibility to viral infection, and impaired embryonic development. 15, 16 G6PD is essential for normal cell growth and survival. For example, G6PD-deficient fibroblasts exhibit retarded growth and premature senescence.…”
mentioning
confidence: 99%
“…[1] Another proposed factor is glucose-6-phophate dehydrogenase deficiency. [2] Age in the range of 6 month to 3 years,[3] fever ≥ 3 days, fever peak ≥ 38.5°C and history of lethargy were also correlated with poor prognosis. [4] On the other hand, older age of the patient was associated with higher risk of EV71 infection.…”
mentioning
confidence: 99%